STUDY OF INDICATORS AND FORMS OF AGGRESSION OF PARTICIPANTS OF MILITARY ACTION IN THE ЕASTERN UKRAINE - Pustovy, Olexander (PSYCHOLOGICAL JOURNAL, 2017)
When performing a combat task for a servant, special features of a person are important. These features are related to personality related to aggression. They are necessary for the preservation of one’s own life, the destruction of the enemy and its objects. These features impose an imprint on the interaction of military personnel in the military team. They are important in the system of socio-psychological factors of the group interaction of servicemen. In group interaction, some features of the personality of a serviceman can appear as aggressive. This can happen in a conflict and have aggressive behavior altogether. These factors have a separate aggressive effect. They manifest themselves in various forms and types of aggression. The question arises as to the definition of indicators of aggression, and the indices of aggression and hostility. Changing aggression rates is a result of group interaction. The change may be larger or smaller. Teamwork of military personnel imprints on the identity of each individual soldier. With proper planning, unit management and personnel management, aggression rates remain within normal limits. During combat stress and frustration, the level of aggression is changing. Aggression is the result of frustration. Aggressive actions are divided into three scales: physical and verbal, active and passive, direct and indirect. Aggression is a combination of three scale scores. It can be manifested in the form of physical aggression, indirect aggression, irritation, negativism, insults, suspicion, verbal aggression, feelings of guilt. The purpose of the study is to determine the rates of aggression of combatants. The study involved participants in combat operations in eastern Ukraine. The study was conducted by the Burs-Durkee Hostility Inventory (BDHI). Indices of aggressiveness and hostility are determined.